A Study of natural material used of Tai-Lue house in Chang Kham, Phayao, Thailand and Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos - Kiattisak Saisaard (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed 1) to study natural material used in Tai Lue house in Chang Kham, Phayao, Thailand, 2) to study natural material used in Tai Lue house in Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos, and 3) to analyze and summarise a natural material used of Tai-Lue houses in Chang Kham, Phayao,Thailand and Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos. There are 5 steps of research: 1) study documents, previous picture of Tai-Lue house and related research and site survey (interview and record) in the areas and focus on natural material used of Thi-Lue houses and type, the technique of the materials of Tai Lue house in Ban Yuan including Moo No. 1 (Ban Sop Wan), Moo No. 2 (Ban Sop Wan), Moo No. 3 (Ban Yuan) and Moo No. 4 (Ban Mang), in Chiang Kham, Phayao, Thailand and Tai Lue houses in Ban Na Yang Tai, Nam Bak, Luang Prabang, Lao People's Democratic Republic; 2) Classify a data of natural material used by sustainable materials methodology of Chris Dancey; 3) Analyzed natural material used and style and technique of Thi-Lue houses; 4) present an analyzed data by exhibition and exchange an idea of natural material used with a local people in ChangKham, Phayao; 5) summarise and recommend natural material used in Tai Lue houses in Chang Kham, Phayao, Thailand and Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos in order to suggest be a guideline on natural material used in the Tai Lue house of Chiang Kham, Phayao in the future. Research findings showed that the study of natural material used in Tai Lue house in Chang Kham, Phayao, and Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos found that it has 5 materials of natural material used; wood (teak), Bamboo, Cogon grass, Dipterocarpaceae leaves (local leave) and water reed in ChangKham, Phayao, Thailand and found that it has a significant material and fibrous organic material; Bamboo as a roof of the house and straw mixed with a clay known as cob in Baan Nayangtai, Mueang Nambak, Luang Phabang, Laos. Technical details and style of natural material used in order to be a guideline for Tai-Lue house and local people in Chang Kham, Phayao..